Root plasticity improves salt tolerance in different genotypes of lentil (Lens culinaris) - Panuccio, Maria Rosaria; Logoteta, Barbara; De Lorenzo, F.; Muscolo, Adele (Ecological Questions, 2011)
Various morphological root parameters were tested in lentil seedlings in a genotype considered salt tolerant (Ustica) and in a salt sensitive one (Eston), grown on salinized soil. Apart from the root biomass production, two ecotypes showed contrasting root morphological responses and these might be partially responsible for dissimilar abilities to tolerate salinity.